Promoting brand relationships - Loureiro, S. M. C. (Journal of Promotion Management, 2019)
Promoting brand relationships (PBR) refers to multiple online–offline relationships established and maintaining among stakeholders (particularly consumers) and also between each stakeholder and a certain brand. This conceptualization starts with the idea that human anthropomorphize inanimate objects and can think about brands as if they were human characters. In fact, brands cannot act, think, or feel by themselves, but can live and evolve through their managers and exist as a partner in a dyadic relationship. In this perspective, the theories of relationship between two partners or individuals can be brought and adapted into the relationship between the consumer and their brands. Some examples of such theories are interdependency theory, relationship investment, and theories of attraction/avoidance. Yet, PBR integrates findings from diverse literature: marketing, advertising, brand management, psychology.